Descriptions of the immature stages and new host plant records of Notozulia entreriana (Berg) (Hemiptera: Cercopidae) pests of grasses in subtropical areas of the Americas - Foieri, Alvaro; Lenicov, Ana M. Marino De Remes; Virla, Eduardo G. (Zootaxa, 2016)
Notozulia entreriana (Berg) (Hemiptera: Cercopidae) is one of the most common spittlebugs inhabiting the subtropical region of the America, inflicting important economic damage to grass crops. The immature stages are described and illustrated; the main characteristics that distinguish instars are the body size, color, number of flagellomeres, and number of tibial and metatarsomere spines. A key for identification of nymphs is provided as a tool to develop field studies.  Nine host plants, all belonging to Poaceae, are recorded as breeding and feeding host plants from different localities in northern Argentina.